Respuesta :
Answer:
2 sqrt(2x-1)
Step-by-step explanation:
f(x) = sqrt(x+7)
g(x) = 8x-11
f(g(x))=
Place g(x) in for x in the function f(x)
f(g(x)) = sqrt( 8x-11 +7)
= sqrt( 8x -4)
Factor out 4
= sqrt( 4(2x-1)
= 2 sqrt(2x-1)
[tex]\\ \sf\longmapsto f(x)=\sqrt{x+7}[/tex]
[tex]\\ \sf\longmapsto g(x)=8x-11[/tex]
- g(x) will be put on the place of x
[tex]\\ \sf\longmapsto f(g(x))=\sqrt{8x-11+7}[/tex]
[tex]\\ \sf\longmapsto f(g(x))=\sqrt{8x-4}[/tex]
[tex]\\ \sf\longmapsto f(g(x))=\sqrt{4(2x-1)}[/tex]
[tex]\\ \sf\longmapsto f(g(x))=2\sqrt{2x-1}[/tex]